The Application Of The Pacta Sunt Servanda Principle In Credit Agreement Disputes: A Study Of Putusan Pn Karanganyar Nomor 36/Pdt.G/2024/PN Krg. - Qoirul Abdul Yahman; Rahayu Subekti; Dona Budi Kharisma (LEGAL BRIEF, 2026)
This study aims to analyze the application of the pacta sunt servanda principle in credit agreement disputes as decided in Putusan Pengadilan Negeri Karanganyar Nomor 36/Pdt.G/2024/PN Krg. The pacta sunt servanda principle is a fundamental principle in contract law which affirms that every agreement made legally is binding on the parties. However, in judicial practice, it is not uncommon for this pronciple to be tested when one party files a lawsuit to cancel the agreement for certain reasons. This study uses a normative juridical method with a legislative and case approach, through analysis of the Civil Code, contract law doctrine, and the judge's legal considerations in the relevant decision. The results of the study show that the application of the pacta sunt servanda principle is not absolute, but must be understood systematically with the principles of justice, propriety, and good faith. Court decisions show that judges have the authority to set aside the validity of an agreement if there is evidence of a defect of consent or a violation of the validity requirements of the agreement. Thus, the principle of pacta sunt servanda remains the main basis for assessing the validity of an agreement, but its application must take into account the balance of rights and obligations of the parties in order to achieve legal certainty that is fair